Effects of acute slackline exercise on executive function in college students - Wen, Ching-Tsai; Chu, Chiung-Ling; Chen, Hsueh-Chih; Chueh, Ting-Yu; Lin, Chih-Chien; Wu, Shao-Yu; Hsu, Wei-Chen; Huang, Chung-Ju; Hung, Tsung-Min (Frontiers in Psychology, 2023)
Background Physical exercise as an intervention for improving cognitive function, especially executive function, is receiving increasing attention because it is easily accessible, cost-effective and promises many additional health-related benefits. While previous studies focused on aerobic exercise and resistance exercise, recent findings have suggested that exercise with high coordination demand elicits beneficial effects on executive function. We therefore examined the effects of an acute slackline exercise on the executive functions of young adults. Methods In a crossover experimental design, 47 healthy participants (21 females), ranging in age from 18 to 27 years (M = 19.17, SD = 1.94) were randomly assigned to different sequences of two conditions (slackline exercise and film-watching). Before and after the 50 min intervention, a modified Simon task was used to assess participants’ executive function (inhibitory control and cognitive flexibility). Results College students showed better inhibitory control performance as indicated by shorter reaction times following acute slackline exercise than those who participated in the film-watching session. As there was no difference in accuracy between the slackline exercise and film-watching sessions, the shortened reaction time after slackline exercise provides evidence against a simple speed-accuracy trade-off. Conclusion Compared with film-watching, acute slackline exercise provides favorable effects on executive function necessitating inhibition in young adults. These findings provide insight into exercise prescription and cognition, and further evidence for the beneficial effects of coordination exercise on executive functions.